2001
DOI: 10.1034/j.1600-9657.2001.170103.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased lifetime prevalence of dental trauma is associated with previous non‐dental injuries, mental distress and high alcohol consumption

Abstract: The purpose of the study was to assess the lifetime prevalence of dental injuries and risk factors involved in a general population-based birth cohort. The study population consisted of 5737 subjects who had participated in a health survey at the age of 31 years. Altogether 52% of the participants were women. This partly computer-based health survey included two questionnaires on previous dental and non-dental injuries, general health, occupational status and lifestyle. The current study was based on these que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 30 publications
0
66
1
3
Order By: Relevance
“…Such injuries are commonly related to falls, or traffic-or sport-related accidents (3)(4)(5)(6). Dental injuries occur more frequently in children between 8 and 15 years of age, although lately there has been a reported increase among patients older than 18 years (7,8). The majority of dental injuries involve the anterior teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Such injuries are commonly related to falls, or traffic-or sport-related accidents (3)(4)(5)(6). Dental injuries occur more frequently in children between 8 and 15 years of age, although lately there has been a reported increase among patients older than 18 years (7,8). The majority of dental injuries involve the anterior teeth.…”
Section: Introductionmentioning
confidence: 99%
“…25 A positive association has also been found between high alcohol consumption and the lifetime risk of dental trauma. 26 Additionally, the prevalence of dental trauma is significantly higher in those that binge drink. 27 Staining There is limited evidence linking alcohol and tooth staining.…”
Section: Traumamentioning
confidence: 99%
“…Of the 13 studies included, one was a case-control study (4), another a cross-sectional analysis of birth cohort data (9) and all others were cross-sectional studies. Due to the marked variation in reference standards for BMI and physical activity, inconsistencies between study outcomes and varying study sizes, the authors reported that the results were inconclusive to declare any true associations (10).…”
Section: Introductionmentioning
confidence: 99%